The Analysis of Social Facts in “The Plague” by Albert Camus - Ali, Muhammad Ilham (ARMADA : Jurnal Penelitian Multidisiplin, 2024)
This research aims to analyze the social facts and interpret quotes that express them in the novel "The Plague" in Oran City, Algeria, and the impacts on society. In this research, the writer used a qualitative method; the data was collected by reading the novel and analyzed using a sociological approach. As the result of this research, there are nine social facts from the book: Social Conditions (Society and Environment), Rat Pest, Health Committee, Epidemic/Plague, Prevention/ Government Rules, Lockdown, and Religious Activities (Prayers and Sermons).